Pengaruh Temuan Sistem Pengendalian Internal, Temuan Kepatuhan Peraturan Perundangan, Tindak Lanjut Hasil Pemeriksaan dan Penyelesaian Kerugian Daerah Terhadap Opini Audit Atas Laporan Keuangan Pemerintah Daerah Kota di Pulau Sumatera - Muhammad Ramadhan Alendra; Henny Yulsiati; Anggeraini Oktarida (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study was conducted with the aim of analyzing the impact of “internal control system findings, compliance with laws and regulations findings, follow-up of examination results, and settlement of regional losses on the audit opinion of the financial statements of municipal governments located on the island of Sumatra”. This study employs a quantitative methodology, utilising secondary data sourced from the official website www.bpk.go.id. The research encompassed 33 cities on the island of Sumatra, comprising a total sample size of 150 individuals. This research employed a purposive sampling technique for sample determination. The hypothesis testing procedure is conducted via logistic regression analysis using Eviews 12 software. The findings indicated that, individually, Internal Control System Findings exert a positive and significant influence on Audit Opinions. The findings regarding adherence to laws and regulations, the follow-up on examination results, and the resolution of regional losses do not significantly impact the audit opinion. Simultaneous testing shows that the variables of Internal Control System Findings, Regulatory Compliance Findings, Follow-Up of Audit Results, and Regional Loss Settlement collectively have a significant influence on the Audit Opinion of the LKPD of the City on the Island of Sumatra.